2014
DOI: 10.3791/52022
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Infection of Murine Embryonic Stem Cell Derived Embryoid Body Cells for Analysis of Hematopoietic Differentiation

Abstract: Embryonic stem cells (ESCs) are an outstanding model for elucidating the molecular mechanisms of cellular differentiation. They are especially useful for investigating the development of early hematopoietic progenitor cells (HPCs). Gene expression in ESCs can be manipulated by several techniques that allow the role for individual molecules in development to be determined. One difficulty is that expression of specific genes often has different phenotypic effects dependent on their temporal expression. This prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The Wnt/β-catenin pathway facilitates an accumulation of β-catenin in the cytoplasm and its eventual translocation into the nucleus to act as a transcriptional coactivator of transcription factors ( 17 ). The results of the present study demonstrated that the expression of β-catenin increased markedly in AOB-treated MEF cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway facilitates an accumulation of β-catenin in the cytoplasm and its eventual translocation into the nucleus to act as a transcriptional coactivator of transcription factors ( 17 ). The results of the present study demonstrated that the expression of β-catenin increased markedly in AOB-treated MEF cells.…”
Section: Discussionmentioning
confidence: 99%